The effect of interactive big book media on beginning reading skills of first-grade students - Innany Mukhlishina; Arinta Rezty Wijayaningputri; Murtyas Galuh Danawati; Exzal Antolyn Febriansyah (University of Muhammadiyah Malang, 2026)
Early reading ability is a very important basic skill for elementary school students because it is the foundation for mastering advanced literacy. This study aims to determine the effect of using Interactive Big Book media on the early reading ability of first-grade students at Muhammadiyah 01 Kepanjen Elementary School. The background of this study shows that students still experience difficulties in recognizing letters, distinguishing similar letter sounds, and understanding simple texts, which is caused by the limited availability of interesting and interactive learning media. This study uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The subjects of the study were 28 first-grade students. Data were obtained through an initial test (pretest) and a final test (posttest) that measured students' early reading ability, and supported by observation and documentation during the learning process. Treatment was given through the application of Interactive Big Book media in three learning meetings that were designed in a structured and interactive manner. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired t-test, and the N-gain test to see the level of improvement in learning outcomes. The results showed a significant increase in students' reading ability after using Interactive Big Book media. The average pretest score of 62.21 increased to 83.14 in the posttest. The t-test results showed a significance value of 0.000, meaning there was a significant difference between before and after the treatment. In addition, the N-gain result of 0.6003 was in the moderate category, indicating a fairly effective increase in reading ability. Thus, it can be concluded that the use of Interactive Big Book media has a positive and significant effect on improving the beginning reading ability of first-grade students at SD Muhammadiyah 01 Kepanjen through more interactive, interesting, and meaningful learning.